PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN PELANGGAN DUNKIN’ DONUTS DI WILAYAH KELAPA GADING JAKARTA UTARA - Venny Lieana; Muhamad Fuad; Bernadine (Jurnal Manajemen, 2021)
In the current era of globalization, culinary developments in Indonesia are very fast. As a result, the types of businesses that have been established vary, ranging from local food to food originating from abroad. With so many types of food that come from abroad and are in great demand, a simple food has emerged, namely donuts. As a food that is in demand, donut companies now have to maintain product quality. In addition to maintaining product quality, donut companies must set competitive prices. The purpose of this study is to determine customer satisfaction at Dunkin 'Donuts in Kelapa Gading, North Jakarta through product quality and price variables, customer satisfaction is the most important thing that must be achieved in a company. The theory used to support this research is Product Quality, Price and Customer Satisfaction. The object of this research is Dunkin 'Donuts in Kelapa Gading, North Jakarta. The data collection technique in this research is by distributing questionnaires online via google form, for the sampling technique used is non-probability sampling and the method used is judgment sampling. The data analysis technique used in this research is validity test, reliability test, descriptive analysis, classical assumption test, and multiple linear regression analysis. The results of this study indicate that the Product Quality variable has t count> t table (3,235> 1.978) with a significance of 0.002 <0.05, for the variable Price has t count> t table (4.182> 1.978) with a significance of 0.000 <0.05. From these results it can be stated that if the level of product quality and price is getting better, it can maintain and even increase customer satisfaction. The conclusion of this study is that all the hypotheses contained in this study have been proven to have a positive effect on Dunkin 'Donuts Customer Satisfaction in Kelapa Gading, North Jakarta. Keywords: Product Quality, Price, Customer Satisfaction